INDIGENOUS KNOWLEDGE SYSTEMS AND PRESERVATION OF EMBROIDERY CULTURE: CASE STUDIES ON LAMBANI EMBROIDERY IN INDIA - Sahu, Bhawna; Tiwary, Anuradha R. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Lambani community is known for its rich and colorful embroidery. The community depends on this art form for their cultural expression. Lambani embroidery is an essential reservoir of historical information and cultural identity passed down through the ages. The research paper will explore the case studies of Lambani embroidery artisans and will examine the functions of Indigenous Knowledge Systems (IKS) in protecting cultural heritage. The paper will provide insight into how Indigenous knowledge, such as traditional symbols, practices, and skills passed down through the ages, is embodied and communicated through Lambani embroidery. On the other hand, lambani embroidery has become commercialized with time and has provided new economic opportunities, especially for women in the community. Commercialization comes with maintaining the craft’s authenticity while meeting the consumers’ demand. The paper will also shed light on the balance between adapting to modern market demands and preserving the traditional culture of Lambani embroidery. It also provides insights into strategies for supporting the sustainable development of traditional crafts while ensuring the continuity of indigenous knowledge. These case studies demonstrate how IKS may be successfully incorporated into modern cultural and economic frameworks while supporting sustainable development and the preservation of cultural heritage.